Study of Norepinephrine Hormone in Patients with Secondary Infertility in Salah Al-Din Province and Assessment of Some Biochemical Parameters - Saleh, Shaimaa Ahmed (American Journal of Bioscience and Clinical Integrity, 2026)
Objective: This study was to evaluate norepinephrine levels among patients with secondary infertility in Salah Al-Din province and among BMI/age groups as a cause of a tool influencing physiological and hormonal homeostasis. The study comprised 80 samples of a 1:1 ratio of patients and control subjects of both sexes and various age groups. The results showed that patients with secondary infertility had lower levels of norepinephrine compared to healthy controls, indicating a problem in the development of the sympathetic nervous system or loss of regulation for catecholamine secretion. However, although there were numerical differences in the norepinephrine levels among the groups studied, these differences did not reach statistical significance with BMI. In terms of age, there was a degree of heterogeneity in norepinephrine levels across different age bands suggesting a modulatory effect of age on norepinephrine secretion, the effect was not the same in all groups.